A SINGLE CENTRE, RANDOMIZED CONTROL TRIAL OF DONOR SITE WOUND DRESSINGS AFTER SPLIT-THICKNESS SKIN GRAFTING - Ismail, Sarosh; Faisal Akhlaque Ali Khan; Sadaf Gulzar; Waqas Sami; Bushra Zulfiqar; Suneel Kumar; Erum Naz (Journal of Ayub Medical College Abbottabad, 2023)
Background: Split-thickness skin grafting (STSG) is a widely employed technique for repairing wounds, such as ulcers, trauma, or in reconstructive surgeries. The objective was to compare the efficacy of different dressing materials for healing donor-site wounds after split-thickness skin grafting. Methods: A single center, randomized controlled trial was conducted at the Department of Plastic Surgery, Civil Hospital Karachi, Pakistan, over a period of six months. The study included patients aged 18 years and above, of both genders, who underwent single donor-site wounds after split-skin grafting with a surface area larger than 10 cm². The eligible patients were randomly divided into six groups: Film, Alginate, Gauze, Hydrofiber, Hydrocolloid, and Silicone. Pain, itching, scarring, complications, and patient satisfaction were evaluated after 12 weeks using standardized assessment scales. Results: The median time to complete wound healing and re-epithelialization varied among the different dressing groups, with hydrofiber and silicone dressings demonstrating the shortest healing time. Statistical analysis revealed a significant difference in the median time to complete wound healing among the dressing groups (p-value=0.019). However, no significant differences were observed in pain, itching, scarring (POSAS observer and patient), or patient satisfaction among the different dressings (p-value>0.05). Conclusion: Although the dressing type did not significantly affect pain, itching, scarring, or patient satisfaction, variations were observed in the time to complete wound healing. These findings contribute to the selection of appropriate donor site dressings for optimizing outcomes in split-skin grafting procedures.